Beton Ramah Lingkungan dengan Ampas Tebu sebagai Substitusi Parsial Semen - Muhammad Rahman Rambe; Noni Paisah; Rizky Febriani Pohan; Alvi Sahrin Nasution (Yayasan Literasi Sains Indonesia, 2025)
Excessive use of cement in construction projects can result in air pollution which can trigger health problems. For this reason, innovation is needed by using environmentally friendly organic materials such as sugarcane bagasse waste as a partial substitute for cement to make environmentally friendly concrete. The use of sugarcane bagasse waste as a partial substitute for cement can prevent environmental pollution due to dust produced by cement. This research aims to make maximum use of sugarcane bagasse waste as a concrete mixture. The method used in this research is an experimental method through the preparation stage, aggregate inspection, job mix design, slump test, making test objects, caring for test objects, testing concrete volume weight and testing concrete compressive strength. The sugarcane bagasse powder used is 0% composition; 2.5%; 5%; 7.5% and 10%. Based on the research results obtained, it can be concluded that the average concrete compressive strength values at variations of 0%; 2.5%; 5%; 7.5% and 10% are 24.08 MPa; 21.98 MPa; 17.67 MPa; 14.54 MPa and 11.66 MPa, respectively. Sugarcane bagasse powder can be used to make environmentally friendly concrete or as a partial replacement for cement. In order to make optimally environmentally friendly concrete, it is recommended that cement be mixed with 2.5% sugarcane bagasse powder.